2023
DOI: 10.2174/1570159x21666221129113942
|View full text |Cite
|
Sign up to set email alerts
|

Substance use Specificities in Women with Psychosis: A Critical Review

Abstract: Background: Women with schizophrenia or other psychotic disorders differ from male patients in many respects, including psychopathology, prognosis, disease course, and substance use comorbidities. Most studies performed to date to investigate the association between drug use and psychosis have not evaluated gender differences, although this has started to change in recent years. Methods: We briefly summarize the available evidence on gender differences in drug use and substance use disorders (SUD) in psychot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 108 publications
(161 reference statements)
0
1
0
Order By: Relevance
“…Women differ in many ways from men with respect to substance use disorders. Casanovas and colleagues [ 63 ] found that all substance abuse disorders were less prevalent in women than in men, though it is possible that they may be underdiagnosed in women. Their use, especially in the case of cannabis, though lower than in men, impacts women’s health more negatively.…”
Section: Resultsmentioning
confidence: 99%
“…Women differ in many ways from men with respect to substance use disorders. Casanovas and colleagues [ 63 ] found that all substance abuse disorders were less prevalent in women than in men, though it is possible that they may be underdiagnosed in women. Their use, especially in the case of cannabis, though lower than in men, impacts women’s health more negatively.…”
Section: Resultsmentioning
confidence: 99%